Topics a Union President Visited to Mobilize Members - Reshef, Yonatan; Keim, Charles (Relations industrielles / Industrial Relations, 2018)
We analyze four calls to action issued by the British Columbia Teachers’ Federation (BCTF) president, Jim Iker. These appeals sought to mobilize members during the 2013-2014 collective bargaining that pitted the BCTF against the British Columbia government and the direct employer, the British Columbia Public School Employers’ Association. We apply a “theory of rhetoric” developed by Chaim Perelman to locate and analyze the topics the BCTF president used to persuade his members to adhere to his arguments about the merit of collective action.We argue that the president constructed his rhetoric by visiting five topics—urgency, fairness, futility, agency, and integrity. The first three promoted a utilitarian logic for collective action. Iker used them to persuade teachers, and other stakeholders, that collective action was necessary for addressing the problem—the futility of the bargaining process to produce a negotiated fair agreement due to the government’s reluctance to bargain in good faith. The last two topics—agency and integrity—comprised a rhetoric of comfort and reassurance offering an affective logic for acting collectively. At least some union members, as well as other stakeholders, might have felt that teachers are expected to care for their charges in the classroom rather than on the picket line, by withdrawing services they monopolize. Iker used the topics of agency and integrity to remind everyone that defending students, young teachers, the teaching profession, and the education system was commendable, and reassured them that collectively they would not be ignored and nor would they fail.In short, we have pointed out five topics that the president visited to mobilize his members to collective action. They highlight a unique rhetoric that aimed to persuade teachers to become agents of protest. Our case study methodology did not allow us to generalize our findings, which more research is, thus, needed to corroborate.